The impact of the COVID-19 pandemic on oral health - Alicja Wójcik; Wojciech Pakaszewski; Klaudia Smulewicz; Bartłomiej Ziomko; Bartosz Rusin (Kazimierz Wielki University, 2023)
The COVID-19 pandemic in Poland is from March 2020 to May 2022. During this time, dental personnel were identified as one of the groups with the highest risk of the virus, resulting in a sanitary regime in dental offices. Numerous restrictions and precautions began to generate additional costs, and patient fear avoided visits. Many offices stopped working during the pandemic period. The aim of this study was to examine the impact that the SARS-CoV-2 virus epidemic had on the level of dental care and on changing oral health habits in Poland. The study, which included 312 individuals, showed a significant increase in endodontic visits and extractions and a decrease in conservative treatments and hygienization performed. Despite the withdrawal of the epidemic state in Poland, the intensity of follow-up visits has still not returned to those prior to March 20, 2020, and the fear of the virus has exacerbated the lingering anxiety of many patients to see a dentist.